Cognitive therapy for challenging problems : what to do when the basics don't work - Beck, Judith S.; Beck, Aaron T. (The Guilford Press, 2005)
Following on the success of the bestselling Cognitive Therapy: Basics and Beyond, this groundbreaking book from Judith S. Beck addresses what to do when a patient is not making progress in cognitive-behavioral therapy. Provided is practical, step-by-step guidance on conceptualizing and solving frequently encountered problems, whether in developing and maintaining the therapeutic alliance or in accomplishing specific therapeutic tasks. While the framework presented is applicable to a range of challenging clinical situations, particular attention is given to modifying the longstanding distorted beliefs and dysfunctional behavioral strategies of people with personality disorders. Helpful appendices include a reproducible assessment tool, and the Personality Belief Questionnaire